Creating trees in Maya/Paint effects (Forest techniques, 2012)
In this DVD-ROM, Alex demonstrates how to use the Paint Effects engine in Maya to create realistic trees. We begin by looking at the default PFX library, which has been converted to polygons for a Mental Ray workflow in an interactive instancer driven scene. Alex than demonstrates how to customize a tree, using a preset library as a starting point. Creating custom textures in Photoshop and setting up miaMaterials is then explored using Physical Sun/Sky and photographic camera exposure. Tree animation with wind turbulence is generated in preparation for incorporating trees into a high-poly park scene. Teachniques for populating the park with trees and other plants are discussed in a dynamic workflow via surface emission, instancing and particle expressions. Alex renders the animated scene, including his ZDepth workflow. In conculusion, a variety of tips for creating custom trees are discussed to make the default library a more useful start point for professional projects.